Perkembangan Islam di Kesultanan Banjarmasin - Ita Syamtasiyah Ahyat (Jurnal Lektur Keagamaan, 2012)
The Sultanate of Banjarmasin is a continuation of the previous Hindu kingdoms, the Negara Dipa and Negara Daha. It began as the settlements of the Malays, then a port for Muslim traders in getting spices and other commodities, the sultanate developed into an important kingdom in South Kalimantan. The development of the empire along with the spread of Islam in the area has made Islam highly influenced the cultural, social, political and economic lives of the empire. Islam, in other words, has brought about a typical civilization of Banjarmasin Sultanate